Information, certification and demand for food safety: Evidence from an in-store experiment in Mumbai - Birol, Ekin; Karandikar, Bhushana; Roy, Devesh; Torero, Máximo (Wiley, 2015)
Is demand for safe food in developing countries low because of limited ability to pay, or because of lack of consumer awareness and absence of credible certification? To answer this question we conducted a controlled market experiment in Mumbai, India, selling grapes with credible certification labels alongside unlabeled grapes while providing randomly selected consumers with information on salient features of food safety certification. We confirm that informed consumers are more likely to purchase labeled grapes, controlling for prior information and attitudes, and using two (intensive versus extensive) information treatments. Policies related to information/certification could be an important component of improving public health by mobilising latent demand for food safety and hence supply of safer food for the public.